Biogas generation from floral waste using different techniques - M.B. Kulkarni; P.M. Ghanegaonkar (Global Journal of Environmental Science and Management)
There is a great need to implement low-cost and user-friendly methods for further propagation of biogas technology in India. Environment unfriendly disposal of floral waste causes serious environmental pollution. Literature shows a limited research work regarding the anaerobic digestion of floral waste for biogas generation.  The present experimental work aims to propagate floral waste as a sustainable source of biogas energy in India. Using different techniques like novel alkaline pretreatment, solar heating of the digester and co-digestion with food waste give enhanced biogas production from floral waste. A novel alkaline pretreatment of the floral waste using sodium carbonate and sodium bicarbonate gives an improvement in biogas output by 106%, with a saving in the cost of chemical pretreatment up to 96%, compared to traditional sodium hydroxide pretreatment. Also, solar heating of the digester increases the biogas output by 122% as compared to digesters in ambient conditions. Co-digestion of the floral waste with food waste also improves biogas output by 32.6%. Raw biogas from floral waste contains over 57% methane, which is higher than the previous studies. Large-scale application of the techniques can benefit the society.